Pengembangan Lembar Kerja Peserta Didik (LKPD) sebagai Media Pembelajaran Biologi Berbasis Android pada Materi Sel di SMA/MA - Hikmatul Azizah; Mulyati Mulyati; Diana Susanti (Journal on Education, 2023)
The learning process requires a medium to achieve learning objectives. One of the learning media used in schools is LKPD. LKPD (Student Worksheets) are needed to support the material in the learning process. The LKPD available in schools is still in the form of sheets like books making students' low interest in reading and working on them. These learning media cannot be used at any time by students (less practical). Student worksheets that exist today need innovation so that they can keep up with the times and will make it easier for students to learn. One of the innovations in learning media that is used in learning is the Android-based LKPD. At SMAN 1 Lunang teachers use LKPD which is still in the form of sheets like books and there is no innovation in learning media. For this reason, it is necessary to develop teaching materials in the form of Android-based worksheets. The research aims to produce Android-based LKPD on cell material that is valid and practical. This Android-based LKPD development research uses a 4-D model. This model has four stages of development, namely define, design, develop and disseminate. This research was carried out until the develop stage, namely the validity test and practicality test. The validity test was tested by a validator consisting of 2 lecturers and 1 biology teacher. The practicality test was assessed by 1 biology teacher. The instrument used is a questionnaire. Data were analyzed descriptively using the percentage formula. The results of the Android-based LKPD validity test with a result of 84.88% with very valid criteria. Practicality test results with a result of 81.11% with very valid criteria. Based on the results of the validity test and practicality test, it can be concluded that this LKPD is very valid and very practical.